Hepatic histopathological structure and change of Scatophagus argus during its juvenile stage from Paknam Pranburi Estuary, Thailand - เสนารัตน์, ศิลปชัย (YRU Journal of Science and Technology, 2018)
The objectives of this research were to examine the hepatic histology and to assess the health of Scatophagus argus during its juvenile stage from Paknam Pranburi Estuary, Thailand using hepatic histopathology as biomarker. Histologically, the liver structure with covering of a capsule was composed of hepatocytes. Each cell had a spherical nucleus and surrounded by eosinophilic cytoplasm. For histopathological alterations, vacuolar degeneration, hyaline degeneration, pyknotic nuclei and karyolysis was occurred in the hepatocytes. In addition, the accumulation of melanomacrophage centers were observed in both some liver areas and blood vessels. As our results indicated that all lesions are related to functional structures in the liver tissue, which has an effect on fish health in Paknam Pranburi Estuary, Thailand.